Microbial Diversity in Freshwater and Marine Environment - Aryal, Sagar; Karki, Gaurab; Pandey, Sunil (Nepal Journal of Biotechnology, 2015)
Water covers seven tenths of the Earth’s surface and occupies an estimated total volume of 1,386,000,000 cubic kilometers (km3). Of all the water found on Earth, 97% is marine. Maximum of this water is at a temperature of 2 to 3°C and devoid of light; 62% is under high pressure (>100 atm). Microscopic phytoplankton and associated bacteria generate a complex food web that can extend over long distances and extreme depths. The marine environment looks so vast that it will not be able to be exaggerated by pollution; however, in coastal areas human activities are increasingly disrupting microbial processes and damaging water quality. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 68-70